(untitled) (Bangladesh Journal of Plant Taxonomy, 2019)
The present study explores detailed morphoanatomical features of five species of Piper L., viz. P. betle L., P. longum L., P. nigrum L., P. retrofractum Vahl and P. sylvaticum Roxb. Each species is supplemented by detailed updated nomenclature, vernacular names, diagnostic characters, phenology, ecology and representative specimens. Maximum number of cortical and medullary vascular bundles have been observed in P. nigrum and P. retrofractum, respectively. In contrast, minimum number of cortical and medullary vascular bundles have been found in P. sylvaticum. Glandular trichomes are found on the midrib of P. betle, P. longum, and P. sylvaticum, whereas trichomes are lacking in P. nigrum and P. retrofractum. The highest number of collateral vascular bundles have been found in P. retrofractum followed by P. nigrum, while P. betle and P. longum contain single collateral vascular bundle. P. betle can easily be distinguished from other species by its oval stem, non-glandular multicellular trichome with pointed tip, and presence of idioblasts and oil droplets. P. longum is distinct from remaining species by its diacytic stomata. Keys to the species based on morphological and anatomical characters are provided for easy identification of the studied species.